2020
DOI: 10.1111/hae.14212
|View full text |Cite
|
Sign up to set email alerts
|

Management of people with haemophilia A undergoing surgery while receiving emicizumab prophylaxis: Real‐world experience from a large comprehensive treatment centre in the US

Abstract: Introduction Surgery is frequently required in persons with haemophilia A (PwHA). Emicizumab, a bispecific, humanized monoclonal antibody, bridges activated factor (F) IX and FX. Management of patients undergoing surgery while receiving emicizumab is of clinical interest due to paucity of data. Aim Review real‐world experience of PwHA with/without FVIII inhibitors who required surgery while receiving emicizumab prophylaxis. Methods Data regarding peri‐operative management, including type of surgery, haemostati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
38
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 13 publications
5
38
0
2
Order By: Relevance
“…Results of the EAHAD survey are mostly in line with these recommendations and with published data from the HAVEN studies and two HTCs in the US 15,16,17 . Regarding bypassing agents, rFVIIa is the treatment of choice for patients with inhibitors on emicizumab 10,11,13,14,16 . Survey results are consistent with this recommendation.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Results of the EAHAD survey are mostly in line with these recommendations and with published data from the HAVEN studies and two HTCs in the US 15,16,17 . Regarding bypassing agents, rFVIIa is the treatment of choice for patients with inhibitors on emicizumab 10,11,13,14,16 . Survey results are consistent with this recommendation.…”
Section: Discussionsupporting
confidence: 78%
“…For example, data on management of inhibitor and non‐inhibitor patients on emicizumab undergoing surgery is currently scarce and no guidelines on a European or global level, only proposals and recommendations on a national level, are available so far 12,13,14 . Results of the EAHAD survey are mostly in line with these recommendations and with published data from the HAVEN studies and two HTCs in the US 15,16,17 . Regarding bypassing agents, rFVIIa is the treatment of choice for patients with inhibitors on emicizumab 10,11,13,14,16 .…”
Section: Discussionmentioning
confidence: 81%
“…During these trials 141/215 (65.6%) of minor surgeries/procedures, including dental and central venous access device removals, were managed without prophylactic coagulation factor, and 128/141 (90.8%) did not result in post-operative bleeding requiring factor replacement. 10 Similarly, Lewandowska et al 3 reported that five out of nine (5/9) vascuport removals were successfully performed with emicizumab as a sole haemostatic agent. Moreover, in an observational study from three haemophilia centres in the United States, one major and 28 minor surgical procedures were performed in PwHA being treated with emicizumab prophylaxis.…”
mentioning
confidence: 99%
“…In the emicizumab era, CVAD devices removal is a common procedure as venous infusions are no longer needed and are replaced by subcutaneous injections. 3 However, there is no consensus on the appropriate management of CVAD removals or other surgical procedures in patients on this novel agent. 4 The safety and efficacy of emicizumab prophylaxis in PwHA have been demonstrated in HAVEN clinical trials programme.…”
mentioning
confidence: 99%
See 1 more Smart Citation